Salvation of o-and p-Nitroanilines in Some Organic Solvent at 25 oC - Gomaa, E.A.; Shallaby, A.M.; Moussa, M.N.H. (Asian Journal of Chemistry, 2010)
From the experimental solubility measurements of o-nitroaniline (ONA) and p-nitroaniline (PNA) in the organic solvents acetonitrile (MeCN). N-methylformamide (NMF), ethanol (EtOH), N-N, dimethylformamide (DMF), propylene carbonate (PC), dimethyl sulphoxide (DMSO), and N-methylpyrrolidone (NMePy), the free energies of solvation (ΔGº), free energies of transfer (ΔGtº) from water to the organic solvents for both solutes and the hydrogen bonding free energies (ΔGºH-bond) for ONA in the organic solvents were evaluated.